TEACHING FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE TO STUDENTS OF NON-LINGUISTIC UNIVERSITIES (Scientific journal of the Fergana State University, 2023)
The formation of communicative competence acts as a leading one in teaching foreign languages. It accurately determines the potential of a future specialist in a particular field, since today the need for specialists with knowledge of a foreign language is increasing.The methods of scientific research as analysis, synthesis, deduction and other theoretical research methods were applied.